TEACHER’S EXPLAINING SKILLS IN THEMATIC LEARNING IN THE THIRD GRADE OF ELEMENTARY SCHOOL - Ahmad Ipmawan Kharisma (Kopertis Region IV Jabar and Banten, 2021)
This research generally aims to describe Explaining skill in the thematic study on teachers in the third grade of elementary school. In particular, the purpose of this research is to describe the Explaining skills of teachers on pre, main, and post activitiesin thematic learning in the third grade of elementary school.This research was a qualitative research particularly descriptive qualitative research. Data collecting methods used consisted of observation, interview with principal, teachers, students, and photo or video collected from learning activities in the third grade of elementary school.It can be concluded thatgenerally the teacher’s Explaining skills in the third gradehad been well mastered and in accordance with the Explaining components. The Expalaining skills on the pre learning activitieswere not perfectly performed because the teacher forgot to convey learning goal and rarely gave an overview of the subjects which would be implemented at the time of opening the lesson. Skills of Explaining on the main learning activities had been suitedwith all indicators of Explaining skills. The post activities had also alreadybeen mastered well. Yet, the teacherrarely evaluated the learning activitties which had been implemented previously and sometimes did not deliver the learning plan for the next meeting.